Meningkatkan Kompetensi Profesional Guru Dalam Menerapkan Model Pembelajaran Quantum Learning Melalui Workshop Di SMP Negeri 4 Percut Sei Tuan Sei Tuan Pada Tahun Pelajaran 2018/2019 - Yusni Siregar (Pusdikra Publishing, 2022)
Quantum Learning Model through workshops at SMP Negeri 4 Percut Sei Tuan Sei Tuan. The method used in this research is the school action research method through 2 cycles, where each cycle has stages: (1) Planning, (2) Implementation and Observation, (3) Evaluation and (4) Reflection. The subjects in this study were teachers who teach at SMP Negeri 4 Percut Sei Tuan Sei Tuan, Percut Regency, with a total of 30 teachers. Data collection techniques used are observation techniques, interviews, questionnaires and documentation studies. The data analysis technique used in this study is to calculate the percentage of teachers who are able to apply the Quantum Learning Model and the percentage of teachers who are unable to apply the Quantum Learning Model in the classroom. The research results show: (1). There was an increase in the number of teachers applying the Quantum Learning Learning Model from 30 teachers, only 22 (73.33%) teachers applied the Quantum Learning Learning Model in cycle I then increased in cycle II to 26 (86.67%) teachers who were able to apply Quantum Learning Learning Model in the learning process in the classroom; (2) There is a decrease in the number of teachers who are unable to apply the Quantum Learning Learning Model, out of 30 teachers, as many as 8 (26.67%) teachers have not been able to apply the Quantum Learning Learning Model in cycle I then in cycle II there is a decrease in the number of teachers who have not able to apply the Quantum Learning Learning Model, being 4 (13.33%) teachers who have not been able to apply the Quantum Learning Learning Model as a whole; (3) The professional competence of teachers in applying the Quantum Learning Learning Model can be improved through workshops.